Development of a Dual-Leaf Automatic Door Prototype Based on Arduino using HC-SR04 Ultrasonic Sensor and Servo Motor - Syaeful Ilman; Tri Nur Arifin; erfiana Wahyuningsih (International Journal Science and Technology, 2025)
This research aims to design and implement a two-leaf automatic door sytem that opens towards the inside by utilizing an arduino microcontroller, HC-SR04 ultrasonic sensor and servo motor. The test results show that the system can work responsively and stably with a good level of detection accuracy and servo movement symmetry. This system has potential to be implemented on a small scale in residential homes, laboratories, or other semi-automatic public spased.